Characterization and properties of palm kernel shell reinforced polyester composites - Nor Mazlina, Abdul Wahab (Universiti Malaysia Perlis, 2011)
Composites of unsaturated polyester (UP)/palm kernel shell (PKS) have been prepared by hand lay-up technique. The effect of filler loading of UP/PKS composites on mechanical properties and morphology were studied. Tensile and flexural tests have been done to determine the effect of filler loading on mechanical properties. The results showed the increased of PKS filler loading have decreased the value of tensile and flexural strengths, but increased in tensile modulus and flexural modulus. A coupling agent (3-APE) was used to improve the mechanical properties of composites. The presence of 3-APE improved the tensile strength, flexural strength, tensile modulus and flexural modulus. The study of scanning electron microscope (SEM) shows that the filler-matrix interaction was improved with incorporation of 3-APE. The effect of chemical modification of PKS with acrylic acid (AA) in UP/PKS composites increased the tensile strength, flexural strength, tensile modulus and flexural modulus. The SEM micrograph showed the treated composites with AA has better dispersion in UP matrix. FTIR spectra show the interaction between PKS and matrix was enhanced with addition of coupling agent.